Критериальное оценивание: возможности использования в педвузе - Утегенова, Б.М. (My University, 2016)
The article deals with the features of criteria-based assessment and the essence of the new assessment. The approaches and principles of the assessment are offered at the article. In this paper the author gives the logical description of using of the possibilities of criteria-basedassessmentin the conditions of the credit system of study in high education.
Keywords: criteria-based assessment; types of assessment; formative and summative assessment; instructional techniques of assessment; assessment content at credit system of education; advancing the results of assessment; subjects of assessment